When the Safe Alternative Is Not That Safe: Tramadol Prescribing in Children - Rodieux, Frédérique; Vutskits, Laszlo; Posfay-Barbe, Klara M.; Habre, Walid; Piguet, Valérie; Desmeules, Jules A.; Samer, Caroline F. (Frontiers in Pharmacology, 2018)
Children represent a vulnerable population in which management of nociceptive pain is complex. Drug responses in children differ from adults due to age-related differences. Moreover, therapeutic choices are limited by the lack of indication for a number of analgesic drugs due to the challenge of conducting clinical trials in children. Furthermore the assessment of efficacy as well as tolerance may be complicated by children’s inability to communicate properly. According to the World Health Organisation, weak opioids such as tramadol and codeine, should be used in addition to paracetamol and ibuprofen for moderate nociceptive pain in both children and adults. However, codeine prescription has been restricted for the last 5 years in children because of the risk of fatal overdoses linked to the variable activity of CYP2D6 which bioactivates codeine. Tramadol has been considered a safe alternative to codeine. However, it is well established that tramadol pharmacodynamic opioid effects, efficacy and safety, are also largely influenced by CYP2D6 activity. For this reason, the Food and Drug Administration recently released a boxed warning regarding the use of tramadol in children. To provide safe and effective tramadol prescription in children, a personalized medicine approach, with dose adaptation according to CYP2D6 activity, would certainly be the safest method. We therefore recommend this approach in children requiring chronic or recurrent nociceptive pain treatment with tramadol. In case of acute inpatients nociceptive pain management, prescribing tramadol at the minimal effective dose, in a dosage form adapted to the child and after clear instructions given to the parents, seems reasonable based on current data. In all other situations, morphine should be preferred for moderate to severe nociceptive pain conditions.